2015
DOI: 10.1080/08941920.2014.970735
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Peoples' Expectations for Forestry in New Brunswick: Are Rights Enough?

Abstract: This article considers how competing interpretations of rights upon forestland affect indigenous peoples' ability to derive benefits from forests, using interviews and an evaluation exercise in 13 First Nations communities in New Brunswick, Canada.We asked first what First Nations expect from provincial forest governance arrangements, and second, what is preventing them from attaining their expectations? Informants attached greatest importance to rights and environmental protection, but tangible outcomes fall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…On a more practical level, the combination of Canada's jurisdictional framework and ineffective forest policy regimes has resulted in "command-and-control" forms of top-down forest governance, which are often rejected by Indigenous communities and regarded as inappropriate and counter-productive for learning and developing agreements (Greskiw andInnes 2008, p. 1941). Indigenous community representatives often have little formal training in forest management, which results in even greater power imbalances in resource governance and, ultimately, a diminished ability to derive meaningful community benefits from development (Wyatt et al 2015). To compound this issue, limitations imposed on First Nations governance structures by the Indian Act make it difficult to develop the appropriate institutional structures necessary to counteract these imbalances (Nikolakis and Nelson 2015).…”
Section: Building Respectful Relationshipsmentioning
confidence: 99%
See 3 more Smart Citations
“…On a more practical level, the combination of Canada's jurisdictional framework and ineffective forest policy regimes has resulted in "command-and-control" forms of top-down forest governance, which are often rejected by Indigenous communities and regarded as inappropriate and counter-productive for learning and developing agreements (Greskiw andInnes 2008, p. 1941). Indigenous community representatives often have little formal training in forest management, which results in even greater power imbalances in resource governance and, ultimately, a diminished ability to derive meaningful community benefits from development (Wyatt et al 2015). To compound this issue, limitations imposed on First Nations governance structures by the Indian Act make it difficult to develop the appropriate institutional structures necessary to counteract these imbalances (Nikolakis and Nelson 2015).…”
Section: Building Respectful Relationshipsmentioning
confidence: 99%
“…Similarly, in a review of the John Prince Research Forest, Sherry (2005) Nations communities' process needs, including incorporation of way of life, values, beliefs, land ethics and knowledge systems. Likewise, in a study of 13 New Brunswick First Nations, Wyatt et al (2015) found that current forest management frameworks are largely failing to meet community expectations for deriving forestry-related benefits. Where this ultimately becomes an issue is when communities feel that their ability to meet their needs is becoming restricted, they may opt for more short-term benefits and adopt practices that are unsustainable in the long-term (Natcher et al 2004).…”
Section: Clear and Relevant Measures Of Successmentioning
confidence: 99%
See 2 more Smart Citations
“…Forests are important for all citizens of both provinces; however, we focus on those participatory processes that are not specifically designed to address the Crown's obligation to consult First Nations. In NB and NS, First Nations' rights over the land were established in formal treaties with the British Crown in the early 18th century, and the Supreme Court of Canada has supported timber rights for First Nations in two cases (Wyatt et al 2015). Regarding general public involvement, numerous published reports have called for more robust, inclusive, and institutionalized public participatory processes (NBDNR 2004, 2005a,b, Select Committee on Wood Supply 2004, Nadeau et al 2007, NSDNR 2011, 2013b.…”
Section: Historical-cultural Forestry Contextmentioning
confidence: 99%